Safety and efficacy of Xiaoyao-san for the treatment of functional dyspepsia: a systematic review and meta-analysis of randomized controlled trials - Ha, Na-Yeon; Lee, Hanul; Jeong, Haein; Ko, Seok-Jae; Park, Jae-Woo; Kim, Jinsung (Frontiers in Pharmacology, 2023)
Objective: Although Xiaoyao-san (XYS) is a popular herbal remedy for indigestion, there is insufficient ev-idence to recommend it as a treatment option for functional dyspepsia (FD). This review aimed to assess the safety and efficacy of XYS in patients with FD, compared to conventional Western medicine (WM). Methods: Two independent reviewers searched for randomized controlled trials (RCTs) using 11 electronic databases, including Medline and Embase, to evaluate therapeutic effects of XYS on FD up to January 31, 2023. The primary outcome was the total clinical efficacy rate (TCE), and secondary outcomes included scores of dyspepsia-related symptoms (DSS) and incidence of adverse events (AEs). The risk of bias was evaluated using the Cochrane collaboration tool, and data synthesis and subgroup analyses were performed using the Review Manager program. Results: Six studies involving 707 participants were included in the meta-analysis. XYS significantly improved TCE compared to WM (RR = 1.15, 95% CI: 1.05, 1.26, P = 0.002) with high heterogeneity (I2 = 59%, P = 0.06). Combination therapy also showed higher TCE than WM alone (RR = 1.22, 95% CI: 1.05, 1.41, P = 0.008), and the heterogeneity was low (I2 = 0%, P = 0.86). The results showed agreater reduction in DSS in the XYS and combination therapy groups than in the WM alone group (SMD = -0.72, 95% CI: -0.90, -0.53, P < 0.00001) with low heterogeneity (I2 = 44%, P = 0.15), especially for abdominal distension and upper abdominal pain. AEs occurred less frequently in the XYS and combination therapy groups than in the WM alone group (RR = 0.20, 95% CI: 0.07, 0.63, P = 0.006), and the heterogeneity was low (I2 = 45%, P = 0.18). The certainty of the evidence for each outcome was rated from “very low” to “high.” Conclusion: This review suggests that XYS is effective and safe for reducing complaints in patients with FD. However, high-quality RCTs should be conducted to establish more convincing therapeutic evidence of XYS for the treatment of FD. Systematic Review Registration: https://www.crd.york.ac.uk/prospero, CRD42020178842.